2020
DOI: 10.1101/2020.09.16.20191791
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Involvement of mutant and wild-type CYSLTR2 in the development and progression of uveal nevi and melanoma

Abstract: Background Activating Gαq signalling mutations are considered an early event in the development of uveal melanoma. Whereas most tumours harbour a mutation in GNAQ or GNA11, CYSLTR2 (encoding G-protein coupled receptor CysLT2R) forms a rare alternative. The role of wild-type CysLT2R in uveal melanoma remains unknown. Methods We performed a digital PCR-based molecular analysis of benign choroidal nevi and primary uveal melanomas. Publicly available bulk and single cell sequencing data were mined to further stud… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…UM can occur de novo or through malignant transformation of a nevus. Studies have shown that choroidal nevi, similar to UM, can harbor G-protein coupled receptor (GPCR) mutations in GNA11 , GNAQ , and CYSLTR2 24 , 25 . Our computational analyses assume that the initial cell is a malignant cell capable of losing the BAP1 gene, whether it formed de novo or growing in a nevus.…”
Section: Discussionmentioning
confidence: 99%
“…UM can occur de novo or through malignant transformation of a nevus. Studies have shown that choroidal nevi, similar to UM, can harbor G-protein coupled receptor (GPCR) mutations in GNA11 , GNAQ , and CYSLTR2 24 , 25 . Our computational analyses assume that the initial cell is a malignant cell capable of losing the BAP1 gene, whether it formed de novo or growing in a nevus.…”
Section: Discussionmentioning
confidence: 99%
“…Digital PCR was performed to measure the copy number values of chromosome 3 and 8q and to confirm mutations in GNAQ, GNA11, EIF1AX and SF3B1. These experiments were carried out using the QX200 Droplet Digital PCR System (Bio-Rad Laboratories, Hercules, USA) following established protocols [22,27,[29][30][31], and two new assays listed in Supplementary Table 1. The presence and pathogenicity of BAP1 alterations was confirmed by targeted Sanger or nextgeneration sequencing and an immunohistochemical staining, both performed as routine diagnostic analyses in two ISO accredited laboratories (Departments of Clinical Genetics and Pathology, LUMC) [16,32].…”
Section: Collection Isolation and Analysis Of Prospective Cohortmentioning
confidence: 99%
“…As another example, in three largescale genomic studies, a variety of complex BAP1 alterations were only identified after using RNA sequencing data in addition to DNA-derived data [21,25,26]. Finally, CYSLTR2 mutant uveal melanomas recurrently showed silencing of the wild-type allele and preferential expression of the p.L129Q mutation [27]. These examples emphasise the value of investigating RNA in addition to DNA to identify the presence and consequences of certain genetic alterations.…”
Section: Introductionmentioning
confidence: 99%